2013
DOI: 10.1002/2013jf002839
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and humidity within a mobile barchan sand dune, implications for microbial survival

Abstract: [1] Although microorganisms play an important role in biological soil crusts and plant rhizospheres in deserts, it is unclear whether temperature and moisture deep within relatively fast moving hyperarid mobile dunes present a suitable habitat for microbes. To inform this question, we report measurements of temperature and humidity from probes initially sunk below the leeward avalanche face of a mobile barchan dune in the Qatar desert, emerging windward after 15 months of deep burial. Despite large diurnal var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 72 publications
0
35
0
1
Order By: Relevance
“…Detailed direct microscopic observations, culturing and sequencing of isolate 16S rRNA genes were performed on samples taken from a single dune in June of 2013. This dune, which we named Nadine (see S1 Table for GPS coordinates), was chosen because it had been extensively studied with respect to sand temperature and humidity, and had yielded clear evidence of in situ microbial activity [ 30 ]. Shotgun metagenomic sequence analysis was performed on DNA extracted from Nadine sands and on DNA extracts from the sands of its nearest neighbor, a smaller dune located approximately 1 km to the north, which we named Michel ( S1 Fig and S1 Table ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed direct microscopic observations, culturing and sequencing of isolate 16S rRNA genes were performed on samples taken from a single dune in June of 2013. This dune, which we named Nadine (see S1 Table for GPS coordinates), was chosen because it had been extensively studied with respect to sand temperature and humidity, and had yielded clear evidence of in situ microbial activity [ 30 ]. Shotgun metagenomic sequence analysis was performed on DNA extracted from Nadine sands and on DNA extracts from the sands of its nearest neighbor, a smaller dune located approximately 1 km to the north, which we named Michel ( S1 Fig and S1 Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Barchan dunes, however, have received little attention [ 29 ]. We recently observed that much of the interior of the barchan dune we studied in Qatar remained moist and cool enough to support microbial activity despite inhospitable ambient conditions at the surface of the dune [ 30 ]. Given that dune moisture content varies with depth [ 30 ], and that dunes migrate at different rates depending on their size, we sought to understand how these factors affect microbial communities on the dunes.…”
Section: Introductionmentioning
confidence: 99%
“…On a smaller scale, in 0.45 m by 2.5 m vertical sections on five dunes in southwestern North America, Ritsema and Dekker (1994) reported variation from 2.0% to 12.6%, 2% to 8.3%, 0.6% to 11.1%, 0.6% to 11.1%, and 0.6% to 5.3%, with wetter regions irregularly positioned at greater depth, representing a residual stage from former rain events. Studies report similar orders of magnitude of variation in desert dunes in Saudi Arabia (Dincer et al, 1974) and Algeria (Fontes et al, 1986), and variation an order of magnitude smaller in Qatar (Louge et al, 2013). That this variation coincides with dunes' internal structure is confirmed by studies with ground-penetrating radar, in which variation of moisture content is associated with strong reflections, revealing the cross-bedding laid down within the dune (Bristow et al, 1996;Neal, 2004;Qian et al, 2014;Schenk et al, 2009).…”
Section: 1029/2018jb015580mentioning
confidence: 83%
“…We suppose that within the dune, with upwind distance from the dune's slip face, 12-m-thick layers in which water content by volume is 1.2% alternate with 4-m-thick layers in which water content by volume is 6%. This corresponds to 9-month dry seasons being followed by 3-month wet seasons, for a dune migrating at a constant velocity of 16 m/year; these conditions may be considered a physically reasonable idealization of those observed by Louge et al (2013) and Berndtsson et al (1996). Under these assumptions, seismic velocities within the dune will have the distributions represented in Figure 8a.…”
Section: Internal Structurementioning
confidence: 96%
“…On peut voir à titre d'exemple, ci-dessous, le résultat de visualisations par fluorescence effectuées sur des grains de sable prélevés en Mauritanie et au Qatar. On découvre pratiquement sur chaque grain de sable une colonie de micro-organismes vivants ou morts (Louge et al 2013).…”
Section: Dune Mouvante -Dune Vivanteunclassified